ANALISIS KUALITAS AIR SUNGAI SAWUR SEBAGAI UPAYA PENGENDALIAN PENCEMARAN AIR DI KECAMATAN SAMBUNGMACAN KABUPATEN SRAGEN TAHUN 2023 - Mistika Ayu Pradani; Pipit Wijayanti; Gentur Adi Tjahjono (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2024)
Sawur River is a river that is the border of Central Java and East Java which has a brown to black color with a bit turbid so that it is polluted. This study aims to 1) identify the water pollution index in the Sawur River, Sambungmacan District, 2) examine efforts to control water pollution in the Sawur River, Sambungmacan District. Data analysis techniques using the pollution index method to determine the status of river pollution and SWOT analysis to formulate water pollution control efforts. Water samples were tested at 8 sample points and laboratory tests were carried out on nitrates, nitrites, ammonia, phosphates, potassium, detergent, and coliform. The results of the water quality laboratory show that there are several parameter elements that exceed the quality standards, namely nitrite, ammonia, and phosphate. The laboratory results are calculated by the pollution index formula, the pollution index is obtained at all points of the sample categorized as light pollution. According to the SWOT analysis, water pollution control efforts are in quadrant IV with a survival strategy. Efforts that can be made to control water quality over pollution are a) improve the provision of complete information, b) improve coordination between agencies on water pollution, c) increase inventory and identification of polluting sources, d) increase supervision of waste disposal, and e) increase public knowledge and participation for water quality control over pollution.